[MG49-LiClO4]:[TiO2-SiO2] Polymer Electrolytes: In Situ Preparation and Characterization. (4th August 2016) - Kang, Oon Lee; Ahmad, Azizan; Hassan, Nur Hasyareeda; Rana, Usman Ali
Abstract : In the present research, [MG49-LiClO4 ]:[HNO3 -THF/TiO2 -SiO2 ] and [MG49-LiClO4 ]:[ClHNO2 -THF/TiO2 -SiO2 ] polymer electrolytes were first prepared through simple stepwise in situ techniques: sol-gel technique and solution-cast technique. [MG49-LiClO4 ]:[HNO3 -THF/TiO2 -SiO2 ] and [MG49-LiClO4 ]:[ClHNO2 -THF/TiO2 -SiO2 ] polymer electrolytes were then characterized through different experimental techniques. [MG49-LiClO4 ]:[HNO3 -THF/TiO2 -SiO2 ] and [MG49-LiClO4 ]:[ClHNO2 -THF/TiO2 -SiO2 ] polymer electrolytes had exhibited significant structural changes upon different salt concentrations. In the present investigation, [MG49-LiClO4 ]:[HNO3 -THF/TiO2 -SiO2 ] and [MG49-LiClO4 ]:[ClHNO2 -THF/TiO2 -SiO2 ] polymer electrolytes had attained maximum ionic conductivities (σ ~ 10 - 7  S/cm at ambient temperature; 10 −4  S/cm at 100°C) upon 25 wt.% salt insertion. [MG49-LiClO4 ]:[HNO3 -THF/TiO2 -SiO2 ] and [MG49-LiClO4 ]:[ClHNO2 -THF/TiO2 -SiO2 ] polymer electrolytes had exhibited distinct conduction mechanisms in similar experimental configuration. [MG49-LiClO4 ]:[HNO3 -THF/TiO2 -SiO2 ] and [MG49-LiClO4 ]:[ClHNO2 -THF/TiO2 -SiO2 ] polymer electrolytes had exhibited different stability characteristics over certain operational condition.